Socioeconomic differences in healthy and disease-free life expectancy between ages 50 and 75: a multi-cohort study - Head J; Chungkham HS; Hyde M; Zaninotto P; Alexanderson K; Stenholm S; Salo P; Kivimäki M; Goldberg M; Zins M; Vahtera J; Westerlund H (Oxford University Press, 2022)
There are inequalities in healthy life expectancy between ages 50 and 75 according to occupational position. These results suggest that reducing socioeconomic inequalities would make an important contribution to extending healthy life expectancy and disease-free life expectancy.\nThere are striking socioeconomic differences in life expectancy, but less is known about inequalities in healthy life expectancy and disease-free life expectancy. We estimated socioeconomic differences in health expectancies in four studies in England, Finland, France and Sweden.\nWe estimated socioeconomic differences in health expectancies using data drawn from repeated waves of the four cohorts for two indicators: (i) self-rated health and (ii) chronic diseases (cardiovascular, cancer, respiratory and diabetes). Socioeconomic position was measured by occupational position. Multistate life table models were used to estimate healthy and chronic disease-free life expectancy from ages 50 to 75.\nIn all cohorts, we found inequalities in healthy life expectancy according to socioeconomic position. In England, both women and men in the higher positions could expect 82-83% of their life between ages 50 and 75 to be in good health compared to 68% for those in lower positions. The figures were 75% compared to 47-50% for Finland; 85-87% compared to 77-79% for France and 80-83% compared to 72-75% for Sweden. Those in higher occupational positions could expect more years in good health (2.1-6.8 years) and without chronic diseases (0.5-2.3 years) from ages 50 to 75.\nConclusion\nBackground\nMethods\nResults